Gender equality in the forest sector will happen - but when? - Bertills, Mathilda; Hilmersson, Frida (SLU/Dept. of Forest Resource Management, 2019)
The Swedish forest sector have under a long time been characterized of a masculine culture but are changing toward a more equal forest sector. With the perspective of composition of board members and board work, methods and actions can be discussed to improve changes toward a more equal board and organisation.